2023
DOI: 10.1002/pssb.202200507
|View full text |Cite
|
Sign up to set email alerts
|

Charge Balanced Vacancy Engineering to Enhance the Thermoelectric Properties of GeMnTe2

Abstract: As a derivative of GeTe and MnTe, GeMnTe2 exhibits a cubic structure with no phase transition. Compared to GeTe, it is considerably cheaper and has a significantly high carrier concentration compared to MnTe, making it an excellent thermoelectric (TE) material with promising applications. Herein, a charge‐balanced vacancy engineering strategy is employed, resulting in a significant improvement in the power factor of GeMnTe2. Furthermore, the density functional theory calculation shows that the doping of Bi and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Na x CoO 2 is one of the exceptions to Mott’s theory. The thermoelectric performance of Na x CoO 2 was found to be driven by spin entropy. ,,, Although Na x CoO 2 is a narrow band gap compound, its thermoelectric performance is hardly influenced by the bipolar effect, and its working temperature extends to 1000 K. Another exception is the recently reported GeMnTe 2 . , GeMnTe 2 also has a narrow band gap less than 0.05 eV, while its maximum zT appears above 800 K. GeMnTe 2 has been indicated to be an anomalous thermoelectric material driven by the spin’s thermodynamic entropy …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Na x CoO 2 is one of the exceptions to Mott’s theory. The thermoelectric performance of Na x CoO 2 was found to be driven by spin entropy. ,,, Although Na x CoO 2 is a narrow band gap compound, its thermoelectric performance is hardly influenced by the bipolar effect, and its working temperature extends to 1000 K. Another exception is the recently reported GeMnTe 2 . , GeMnTe 2 also has a narrow band gap less than 0.05 eV, while its maximum zT appears above 800 K. GeMnTe 2 has been indicated to be an anomalous thermoelectric material driven by the spin’s thermodynamic entropy …”
Section: Introductionmentioning
confidence: 99%
“…10,11,35,36 narrow band gap compound, its thermoelectric performance is hardly influenced by the bipolar effect, and its working temperature extends to 1000 K. Another exception is the recently reported GeMnTe 2 . 37,38 GeMnTe 2 also has a narrow band gap less than 0.05 eV, 39 while its maximum zT appears above 800 K. GeMnTe 2 has been indicated to be an anomalous thermoelectric material driven by the spin's thermodynamic entropy. 40 In spite of the high carrier concentration, some studies observed the strong bipolar-like effect in GeMnTe 2 .…”
Section: ■ Introductionmentioning
confidence: 99%